Social Graphic Design and its Reflection in Combating Drug Abuse: محمد عباس مظهر الزيدي (Al-Academy, 2021)
Social graphic design is the design that realizes the role and responsibility of the designer in society, and the use of graphic design in bringing about social change, especially as it is a professional contribution that plays an important role in the behavioral development of societies, and through the above, the researcher found a logical justification for his research problem, which is summarized by the following question: (What is the concept of Social Graphic Design and its implications in the fight against drug abuse)While the two objectives of the research were identified in defining the social graphic design and its effect on combating drug abuse, and the theoretical framework was divided into two topics, the first study dealt with the concept of social design, social theories and behavioral and psychological concepts, while the second topic focused on modern communication means and their impact on social design and in the third chapter it was described Two samples were analyzed and a set of results were extracted, the most important of which are (the awareness poster achieved exploration, knowledge and motivation of the community to interact positively with the poster through the word and image within the technical practical framework), and the researcher concluded that the awareness posters are the most important concepts of social graphic design due to their socially circulating intellectual concepts as Translate to community sentiment.